IMPLEMENTASI PROGRAM BERAS MISKIN (RASKIN) DI KELURAHAN ROWOSARI KECAMATAN TEMBALANG KOTA SEMARANG - Dewi Nurul Aisyah; Herbasuki Nurcahyanto; Slamet Santoso (Journal of Public Policy and Management Review, 2014)
Beras Miskin (Raskin) Program is a program of food subsidies as a form of government efforts to increase food security and provide protection to poor families through the distribution of rice. Each family will receive a minimum of 10 kg/month with Rp 1,600/kg at the point of distribution. Researchers take focus in Kelurahan Rowosari Kecamatan Tembalang, Kota Semarang. In fact, implementation of Raskin policy is not always consider full-on procedure policy as depending on condition and situation in society. The objective of this study is to analyze the implementation of the Beras Miskin (Raskin) program. This research uses qualitative descriptive method. Data collection was carried out with in-depth interviews from various informants have been determined. In qualitative research, data retrieved from various sources by using a technique of collecting data of which various (triangulation) and continuously until it is saturated. The result of this research is the determining factors of Beras Miskin (Raskin) program implementation in Kelurahan Rowosari Kecamatan Tembalang, Kota Semarang caused by attitude factors (disposition) which is less successful in rice quality, target the household beneficiaries raskin, the number of households that received rice target beneficiaries.